External blockade of the major cardiac delayed-rectifier K+ channel (Kv1.5) by polyunsaturated fatty acids. - Honoré, E (1994)
The present work shows that arachidonic acid and some other long chain polyunsaturated fatty acids such as docosahexaenoic acid, which is abundant in fish oil, produce a direct open channel block of the major voltage-dependent K+ channel (Kv1.5) cloned in cardiac cells. The inhibitory action of these selected fatty acids is seen when they are applied extracellularly but not when they are included in the patch pipette. Fatty acids then appear to bind to an external site on the Kv1.5 channel structure. Inhibition of Kv1.5 channel activity by polyunsaturated fatty acids (acceleration of the apparent inactivation and decrease of the peak current) is similar to that produced by the class III antiarrhythmic tedisamil. Docosahexaenoic acid and arachidonic acid also inhibit the delayed-rectifier K+ channel currents in cultured mouse and rat cardiomyocytes. These results are discussed in the light of the reported fatty acids effects on cardiac function in diseased states. Since Kv1.5 is also present in the brain, the results reported here could also have a significance in terms of processes such as long-term potentiation or depression.